Perkembangan Industri Perbankan Syariah pada Pembiayaan yang Disalurkan (Libraryresearch) - Ade Irvi Nurul Husna; Arman Paramansyah (Masoem University, 2020)
A number of indicators can show developments in the Islamic banking industry in Indonesia. The purpose of this study is to describe and interpret the results of observations regarding the Development of the Sharia Banking Industry, especially in Financing Distributed (PYD) in Indonesia. This research is a descriptive qualitative research with the approach used is library (library research) in which the collection of data and information obtained from library sources (readings) derived from books, journals, articles, and other reading material that has relevance to the topics in this research. Observations were made by examining the theories, concepts, statistical data, and regulations related to this research. So that in each analysis the main reference is found in the source of data concerning the development of the Islamic banking industry, especially in the financing channeled. The results of the study show that the PYD in the Islamic banking industry continued to show an increase from 2015, 2016, 2017, 2018 and 2019. In 2019 the PYD was at 343 trillion rupiah with a growth percentage of 12.94%.